Sentidos da leitura literária para a formação leitora : análise de publicações na Biblioteca Digital Brasileira de Teses e Dissertações (BDTD) - Anjos, Karllene Silva dos (2021)
This master thesis is linked to the Postgraduate Program in Education of the Federal University of Mato Grosso, Campus of Rondonópolis (PPGEdu/UFMT), in the research line: Languages, Culture and Knowledge Construction: historical and contemporary perspectives, and to the group Alphabetization and School Literacy (ALFALE/UFMT). Through the mapping of studies of dissertations and theses that other researchers published about “education of the literary reader”, this research was conducted around four macro-categories: reading, literary reading, literature and reading education, in order to analyze meanings of literary reading for reading education. As reference, it was used the publications available on the database of the Brazilian Digital Library of Dissertations and Theses (BDTD), in the address: http://bdtd.ibict.br. The analyzed corpus arose from a search for documents, in which it was identified the presence of the descriptors “reading education” “literary reading” in the body of the text. Following that, the filter used was “literature” for the delimitation of the subject. The investigation of the published researches considered the interval from 2002 to 2019 as spatial temporal for year of defense. Of the documents found, it was verified a total of 51 publications, being 37 theses and 14 dissertations. The main question was finding an answer to the following inquiry: What are the meanings of literary reading for reading education in dissertations and theses available on BDTD? The main objective of the research was to analyze meanings of literary reading for reading education in dissertations and theses available on BDTD, and it unfolds in the following specific objectives: for a more quantitative approach: relate institutions that dedicate themselves the most to the study of the theme of this research; identify authors who are most cited and the confluence between them concerning the education of the literary reader; map the main theoretical and methodological references used in dissertations and theses; for a more qualitative approach: investigate what are the definitions attributed by the researchers to each one of the four macro-categories in the definitions selected to compose the corpus of this research. The research is documentary, of the type state of knowledge, and as methodology of data interpretation it was used Content Analysis proposed by Bardin (2010). The theoretical framework of the research was constituted by authors who discuss reading, literature, literary reading and reading education, such as: Foucambert (1994), Silva (2003), Kleiman (2011), Lajolo (1981), Eco (2006), Colomer (2007), Zilberman (2009), Orlandi (1996), Cosson (2018), Candido (1994), Soares (2006), Martins (2006), Bakhtin (1997), Iser (1999), Jauss (1994), and others. The theoretical discussions around the macro-categories subsidized the investigation and the analysis of meanings. Therefore, it is expected that this study contributes with researches about literary reading for reading education.